Comparison of glutathione levels measured using optimized monochlorobimane assay with those from ortho-phthalaldehyde assay in intact cells - Čapek, Jan; Hauschke, Martina; Brůčková, Lenka; Roušar, Tomáš (My University, 2017)
Fluorometric glutathione assays have been generally preferred for their high specificity and sensitivity. An additional advantage offered by fluorescent bimane dyes is their ability to penetrate inside the cell. Their ability to react with glutathione within intact cells is frequently useful in flow cytometry and microscopy. Hence, the aims of our study were to use monochlorobimane for optimizing a spectrofluorometric glutathione assay in cells and then to compare that assay with the frequently used ortho-phthalaldehyde assay. We used glutathione-depleting agents (e.g., cisplatin and diethylmalonate) to induce cell impairment. For glutathione assessment, monochlorobimane (40μM) was added to cells and fluorescence was detected at 394/490nm. In addition to the regularly used calculation of glutathione levels from fluorescence change after 60min, we used an optimized calculation from the linear part of the fluorescence curve after 10min of measurement. We found that 10min treatment of cells with monochlorobimane is sufficient for evaluating cellular glutathione concentration and provides results entirely comparable with those from the standard ortho-phthalaldehyde assay. In contrast, the results obtained by the standardly used evaluation after 60min of monochlorobimane treatment provided higher glutathione values. We conclude that measuring glutathione using monochlorobimane with the here-described optimized evaluation of fluorescence signal could be a simple and useful method for routine and rapid assessment of glutathione within intact cells in large numbers of samples.
Srovnání hladin glutathionu stanovených pomocí optimalizované monochlorobimanové metody a s pomocí o-ftalaldehydu u intaktních buněk
Keywords: Cell impairment; Fluorescence; Glutathione assay; Monochlorobimane; Ortho-phthalaldehyde; Poškození buněk; fluorescence; stanovení glutathionu; bimany; o-ftaladehyd